A case report of successful stent implantation through a fractured stent-strut in a superficial femoral artery based on bench testing simulation. Issue 7 (1st July 2021) - Yamane, Haruya; Kosugi, Shumpei; Date, Motoo; Ueda, Yasunori
Abstract: Background: Stent implantation through the stent-strut of a previously implanted self-expandable stent in the superficial femoral artery (SFA) is not usually performed because the additional stent cannot dilate sufficiently. The key point to achieve sufficient expansion of an additional stent is to break the stent-strut of the previously implanted stent. However, there is no report of how to break the stent-strut. Case summary: A 72-year-old man was admitted to our hospital with acute rest pain and coldness of his left leg; he was diagnosed with acute limb ischaemia. The angiogram demonstrated a fractured stent as well as stent occlusion in the left distal SFA. The guidewire could pass only through the stent-strut because of stent fracture. Fortunately, balloon angioplasty through the stent-strut and thrombolysis achieved successful revascularization. Thereafter, an additional stent was implanted in an attempt to manage the fractured and deformed stent. To obtain sufficient expansion of the additional stent, an experimental study to examine the balloon diameter and pressure to break the stent-strut was performed. Based on the results of the experiment, the stent-strut was successfully broken, and the additional stent was expanded through the stent-strut on the second intervention. Discussion: If an additional self-expandable stent is deployed through the stent-strut directly, it would not be sufficiently dilated. The key point in such a case is to break the stent-strut of the previously implanted stent by balloon inflation before deployment of the additional stent. The experimental study examined the balloon diameter and pressure that can break the stent-strut. This information would be useful when we implant an additional stent through a stent-strut.